2022
DOI: 10.1038/s41598-022-12440-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against the “anomalous-is-bad” stereotype in Hadza hunter gatherers

Abstract: People have an “anomalous-is-bad” stereotype whereby they make negative inferences about the moral character of people with craniofacial anomalies like scars. This stereotype is hypothesized to be a byproduct of adaptations for avoiding pathogens. However, evidence for the anomalous-is-bad stereotype comes from studies of European and North American populations; the byproduct hypothesis would predict universality of the stereotype. We presented 123 Hadza across ten camps pairs of morphed Hadza faces—each with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 72 publications
(80 reference statements)
1
12
1
Order By: Relevance
“…This view entails the troubling prospect that an aversion to anomalous facial features may reflect a deeply embedded feature of our cognitive architecture, rendering the anomalous-is-bad stereotype difficult to mitigate. Our findings, however, are consistent with recent evidence that the anomalous-is-bad stereotype might not be attributable to pathogen avoidance but is instead be learned (Workman et al, , 2022.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This view entails the troubling prospect that an aversion to anomalous facial features may reflect a deeply embedded feature of our cognitive architecture, rendering the anomalous-is-bad stereotype difficult to mitigate. Our findings, however, are consistent with recent evidence that the anomalous-is-bad stereotype might not be attributable to pathogen avoidance but is instead be learned (Workman et al, , 2022.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, facial anomalies can be treated like expressions of infectious disease. A recent cross-cultural study with the Hadza hunter-gatherers of Tanzania casts doubt on an overgeneralized pathogen avoidance account, however, suggesting instead that the anomalous-is-bad stereotype is learned (Workman et al, 2022). Repeated exposure to negative depictions of people with anomalous faces-in movies and other media, for instancemay strengthen reflexive negative emotional responses elicited by anomalous faces that drive negative affective behaviors like social avoidance (Amodio & Cikara, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has consistently demonstrated that facial anomalies negatively affect perceptions of warmth (e.g., trustworthiness), with less consistent evidence for a negative effect on perceptions of competence (Bilici et al, 2022;Jamrozik et al, 2019;Workman et al, , 2022. In contrast to these studies, however, we did not uncover evidence that facial anomalies influenced perceptions of warmth let alone competence.…”
Section: Discussioncontrasting
confidence: 99%
“…We first predicted that participants would give more money to partners with anomalous relative to non-anomalous faces, regardless of whether they enhanced, which could be motivated by feelings of pity or sympathy (Andreasen & Norris, 1972;Rumsey & Bull, 1986). Alternatively, participants could give less money to partners with anomalous relative to non-anomalous faces regardless of enhancement, which would align with evidence-albeit mixed-that facial anomalies are associated with worse competence that would render them less likely to pass the memory test (Jamrozik et al, 2019;Workman et al, , 2022.…”
Section: Introductionmentioning
confidence: 96%
“…More positive impressions of attractive people are related to the "halo effect" (Eagly et al, 1991), a tendency to assess others positively in many areas based on at least one positive judgment about them. As a complement to the "beauty-is-good" stereotype, an "anomalous-is-bad" stereotype posits that people with visible facial differences are seen not only as less attractive but also as less moral (Jamrozik et al, 2019;Workman et al, 2022).…”
mentioning
confidence: 99%